2020
DOI: 10.1093/ofid/ofaa426
|View full text |Cite
|
Sign up to set email alerts
|

Solar Ultraviolet Radiation and Vitamin D Deficiency on Epstein-Barr Virus Reactivation: Observational and Genetic Evidence From a Nasopharyngeal Carcinoma-Endemic Population

Abstract: Background We investigated the relationship of Epstein-Barr virus viral capsid antigen (EBV VCA-IgA) serostatus with ambient and personal ultraviolet radiation (UVR) and vitamin D exposure. Methods Using data from a multicenter case-control study, we included 1026 controls subjects in 2014-2017 in Hong Kong, China. Odds ratios (ORs) and 95% confidence intervals (CIs) of the association between UVR exposure and EBV VCA-IgA (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“… 32 , 34 Our case-control study in Hong Kong, China, also reported similar association between smoking and NPC with and without adjusting for salted fish intake (data not shown). 68 Although our results may be influenced by EBV infection and activation, EBV may not be a confounder but a mediator of the association between smoking and NPC. We did not collect information on reasons for quitting (whether stopped by choice or because of illness).…”
Section: Discussionmentioning
confidence: 67%
“… 32 , 34 Our case-control study in Hong Kong, China, also reported similar association between smoking and NPC with and without adjusting for salted fish intake (data not shown). 68 Although our results may be influenced by EBV infection and activation, EBV may not be a confounder but a mediator of the association between smoking and NPC. We did not collect information on reasons for quitting (whether stopped by choice or because of illness).…”
Section: Discussionmentioning
confidence: 67%
“…The intraassay coefficient of variation was 4.3-8.1% by repeating measurements of 50 samples, and the reliability coefficient was acceptable (< 10%). Circulating 25OHD was classified into three a priori categorizes based on clinically relevant cut-off points for the main analysis: < 37.5 (deficient), 37.5 < 75 (insufficient), and ≥ 75 (sufficient) nmol/L [31].…”
Section: Covariate Assessmentmentioning
confidence: 99%
“…We also hypothesized vitamin D exposure was associated with EBV reactivation. Indeed, our recent study found higher sunlight exposure was associated with EBV VCA-IgA seropositivity in our hospital controls, but circulating 25OHD and genetic predicted 25OHD levels were not associated with EBV VCA-IgA serostatus [26]. The association between UVR and NPC may be positive via EBV reactivation due to UVR-induced immunosuppression [48].…”
Section: Discussionmentioning
confidence: 62%
“…European studies in patients with multiple sclerosis reported inverse associations between vitamin D exposure and EBV serostatus [23e25]. Our recent study [26] showed personal UVR was associated with EBV viral capsid antigen (VCA-IgA) seropositivity, but not with observational or genetic 25-hydroxyvitamin D (25OHD) levels in Hong Kong, where UVR levels are high due to its latitude (22.3 N) yet vitamin D deficiency is common [27]. Given the close relation between EBV and NPC, we hypothesized vitamin D deficiency could have a role in the etiology of NPC.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation